The development of solar irriadiation levelling system using colour contour approach - Abd.Hadi, Faezah (2012)
This project presents the development of solar irradiance levelling spectrum using colour contour approach. The system developed by using the General User Interface (GUI) Matlab. The advantage of the system is irradiation data being easily analysed by the user. Furthermore, the system reduces the time taken to calculate the energy of each level and the total energy of solar irradiation. The irradiance levelling is using three specific colour ranges according to three level of the system. The result from the GUI Matlab shows the data being levels into maximum, medium and minimum level. The specific colours uses are red, yellow and green. Microsoft Excel was used to prove the calculation of energy and total energy and the comparison of the graph in GUI.